Observation of a Large‐Amplitude Slow Magnetosonic Wave in the Magnetosheath. Issue 12 (19th December 2019) - Zhao, S. Q.; Xiao, C. J.; Wang, X. G.; Pu, Z. Y.; Shi, M. J.; Liu, T. Z.
Abstract: Using the Magnetospheric Multiscale spacecraft, we report observations of the pressure‐balanced structures in the form of slow magnetosonic waves rather than the mirror mode description in the Earth's magnetosheath. The slow magnetosonic waves are identified with three criteria: (1) The significant inverse correlation coefficients between the plasma thermal pressure ( P plasma ) and the magnetic pressure ( P mag ) with the constant total pressure ( P tot  =  P plasma + P mag ); (2) the wave frequency Doppler shifted to the plasma flow frame is not zero to within the measurement error, which distinguishes the slow magnetosonic mode from the mirror mode; and (3) the observational dispersion relation is in a reasonable agreement with the linear theoretical result of slow magnetosonic waves. We find that slow magnetosonic waves can propagate over many wavelengths with negligible decay due to their transverse propagation which dramatically decreases their kinetic damping rate. Furthermore, we propose a possible generation mechanism that a high‐speed ion beam resonates with the local ion acoustic mode contributing to the inverse Landau damping process that converts particle energy into waves. Key Points: We report observational evidence of a large‐amplitude slow magnetosonic wave propagating transverse to the magnetic field in the magnetosheath To within the measurement error, the wave frequency Doppler shifted to the plasma flow frame (0.1±0.017)ωci is not zero, which distinguishes the slow magnetosonic mode from the mirror mode Both the dispersion relation and the anti‐correlation between magnetic and plasma thermal pressures are used to uncover the existence of slow magnetosonic waves